Disproportionate Vertebral Bodies and Their Impact on Lumbar Disc Herniation - Ralph Läubli (Journal of Clinical Medicine, 2021)
Background: The aim of this study was to determine whether the presence of disproportionate vertebral bodies is a risk factor for disc herniation (DH). Methods: Sixty-seven consecutive patients (m: 31 f: 36) who underwent lumbar discectomy for symptomatic DH at one level between L3 and S1 were retrospectively included. The last three motion segments (3 × 67 = 201) were assessed on sagittal MRI scans. A disproportionate motion segment was defined as the difference of more than 10% of the antero-posterior diameter of two adjacent endplates. Results: DH was present in 6/67 (9%), 26/67 (38.8%), and 35/67 (52.2%) patients at L3/4, L4/5, and L5/S1, respectively. A total of 14 of 67 patients demonstrated a disproportionate motion segment at the discectomy level (20.9%). A total of 23 of the 201 (11.4%) investigated motion segments met our criteria for a disproportionate motion segment. In our study population, when one of the 201 segments was disproportionate, the positive predictive value (PPV) for DH increased toward the lower segments: the PPV at the L5/S1 level was 83.0%. The odds ratio of disproportion for DH was the highest at the L5/S1 level, with 6.0 ± 0.82 (p = 0.017). Conclusions: The presence of a disproportionate motion segment in the lower spine may lead to a significant higher risk for DH in patients undergoing discectomy.